The Global Research Landscape of Knee Osteoarthritis Pain Management: A Bibliometric Analysis - Ghazali , Mazira Mohamad; Ismail, Samhani; Mohd Zain, Muhammad Rajaei Ahmad; Abdullah , Jafri Malin; Juahir, Hafizan; Jusoh, Mohd Hanifah (Bangladesh Journal of Medical Science, 2025)
Background Knee osteoarthritis (OA) is a significant public health concern among the elderly due to the global aging population. It is a widespread and crippling type of joint ailment that results in pain and immobility for millions around the globe. Nonetheless, even with such treatments like medications and physical therapy, effective pain management remains a significant challenge. This study aimed to measure the quantitative impact of publications in knee OA and its pain management. Materials and methods Article titles from the Scopus database were screened as of March 31, 2024, utilizing keywords related to knee OA and pain management or conservative therapy. The documents underwent frequency analysis using Microsoft Excel, data visualization employing VOSviewer, and citation metrics analysis using Harzing’s Publish or Perish software. Results and discussion A total of 1087 documents analyzed revealed a consistent upward trajectory in the number of publications focused on knee OA and pain management strategies since 1975 until March 2024. The United States of America (USA) ranked first as the leading contributor to research activity in this field. The analysis encompassed contributions from 160 scholars representing 77 countries and 160 institutions. The publications spanned articles in multiple languages and involved multiple authors. In terms of publication numbers, the top three institutions were the University of Sydney, the University of Melbourne, and Harvard Medical School. Conclusion This study provides a comprehensive bibliometric overview of the published literature on pain management strategies for knee OA patients over the past five decades. The findings underscore the need for future research efforts to prioritize the exploration of novel pain management approaches for individuals with knee OA, as well as elucidate the underlying mechanisms contributing to pain manifestation in this patient population. Continued interdisciplinary collaboration and knowledge dissemination will be crucial in advancing our understanding and management of knee OA-related pain. BJMS, Vol. 24 No. 03 July’25 Page : 746-763